Research Mapping on Historical Heritage in historical learning: a Bibliometric Analysis From 2005-2025 - Yuver Kusnoto; Adi Wiranata (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
Research on historical heritage is crucial not only for the physical preservation of heritage assets but also for sustaining their cultural meanings and functional values for present and future generations. Educational institutions play a strategic role in transmitting these values by integrating historical heritage into history learning processes. This study aims to map the development and research trends of historical heritage in the context of history education through a bibliometric analysis. A systematic search of the Scopus database was conducted for publications published between 2005 and 2025, resulting in 223 eligible articles. Bibliometric visualization and network analysis were performed using VOSviewer to identify influential authors, institutions, countries, and thematic clusters. The results indicate that Spain leads the field in terms of publication output, citation impact, and international collaboration. Maria Feliu was identified as the most influential author, while Universidad de Murcia, Universitat de Barcelona, and Universidad de Extremadura emerged as the most prominent institutions. The thematic analysis revealed four major research clusters, with virtual reality and augmented reality emerging as dominant and rapidly growing themes. These findings highlight a significant shift toward technology-enhanced heritage-based learning and underscore the increasing relevance of immersive technologies in advancing meaningful and engaging history education